Exploration of Moroccan EFL University Students’ Retrospective Knowledge of Cognitive and Metacognitive Reading Strategies in Processing Advanced-level Written Discourse in English - Msaddek, Mohammed (International Research in Education, 2023)
Based on my unpublished Doctoral Dissertation (Defended in 2015) that investigates the impact of explicit reading strategy instruction on Moroccan EFL university learners’ (meta) cognitive reading strategy use and reading achievement, the present exploratory study reflects the extent to which the learners are retrospectively conscious of the (meta) cognitive reading strategies (RSs) that facilitate the assimilation and comprehension of the textual input. It addresses 113 English department university students belonging to two groups (Group 1: N= 50; Group 2: N= 63) studying at the first-semester level. The data were obtained through the dependence on two advanced-level EFL reading comprehension texts (i.e., narrative, expository) which were accompanied by a retrospective questionnaire (RQ). The results evince that, given that the targeted two groups unconsciously used some (meta) cognitive reading strategies (RSs) for attaining the textual comprehension, their retrospective consciousness of the core nature and essence of these metacognitively-oriented strategic moves is typically typified by utmost inadequacy. Finally, some useful recommendations relative to both EFL reading research and pedagogy as well as some unavoidable limitations are presented.